Content analysis of apps and video games: Implications in cognitive processes in initial reading - Ana María Jiménez Porta; María Evelyn Diez-Martínez Day (Universidad de Guadalajara, 2018)
he present study reports on the analysis of the contents of 20 apps and video games, to determine if these can favor the development of cognitive processes involved in initial reading in Spanish. The analysis aims to provide, to the clinical and educational studies, specific information on the type of tasks covered in their contents, to assist in the process of literacy in Spanish. The instruments used for data collection were, direct observation, analysis of content based on the tasks performed in the games and applications, and the classification of these tasks based on the literature on the topic. Structured observation determined that most applications promote reading learning in different levels, and only 4 of them favor writing; among the latter, a game of virtual reality (Minecraft), promotes reading and writing during the activity in the game. The results show the relevance of the analysis of the tasks involved in video games and applications, to determine if they can be used as tools mediators of specific cognitive processes within the formal, non-formal educational environments, and clinical educational environments.